From control to cohabitation: Social-ecological insights on urban wildness narrative - Collier, Marcus; O'Donnell, Mairad (My University, 2026)
Narratives surrounding urban green space management have experienced significant shifts in recent years. While the command-and-control approach to urban green space management was once a dominant narrative, alternative understandings have emerged over time. The emerging narrative on urban wilding presents a unique opportunity to expand on our current understandings and approaches to urban green space management. This research explores how participation in experiential workshops that engage with urban wild spaces (UWS) through deliberative methods may influence our narratives of urban green spaces and their management. This is achieved by examining the human-nature dynamics of the workshops, which employ methods of wild transect walks, storytelling, and multispecies role-playing, framed by social-ecological traits to facilitate the translation of perceptions and values. The workshops gathered data on the interplay between the participating human stakeholders. Based on a narrative analysis, the findings suggest that an initial disconnect between humans and ecology appears during engagement with UWS. Throughout the sense-making and sharing process, participants begin to connect with the spaces through sensory effect traits, such as auditory elements, tactile sensations, and visual characteristics, as they recount childhood memories and stories about the ecosystem's ecology. Narratives then shift as the workshops progress; participants move from descriptions of practical management and control toward a more ethical understanding of cohabitation. The article concludes by suggesting directions for future research to further understand the driving factors behind these shifting narratives.
PUBLISHED
This research examines how peoples ideas about managing urban green spaces are evolving. In the past, management often focused on control, maintaining order and tidiness in nature. Recently, new approaches have emerged, such as urban wilding, which promotes allowing nature to grow and evolve more freely. This study tested whether workshops could alter peoples perceptions of urban green spaces. During the workshops, participants explored urban wild areas through activities like wild walks, storytelling, and role- playing as different species. These activities encouraged individuals to notice sensory details (such as sounds, textures, sights), and to share personal memories and stories. At first, many participants felt disconnected from the wild areas. But as the workshops progressed, they began to connect more deeply, moving away from seeing nature as something to control towards seeing it as something to live alongside and share. The study concludes that these kinds of participatory workshops can help people develop more ethical and coexisting relationships with urban nature. It also suggests that more research is needed to understand what drives these shifts in perspectives.
Keywords: Inclusive Society; Smart & Sustainable Planet; Biodiversity; Biodiversity and Conservation; Green space management; Informal wild spaces; NOVEL ECOSYSTEMS; Narrative research; Participatory Research Methods; Qualitative Methodology & Methods; Urban Ecology; Urban Sociology; Urban Wildness; Community; Environment and housing; Policy; Social participation